2020
DOI: 10.3390/agronomy10101589
|View full text |Cite
|
Sign up to set email alerts
|

10-Years Studies of the Soil Physical Condition after One-Time Biochar Application

Abstract: The ten-year experiment on the soil physical properties of biochar-amended Podzol was studied. Biochar was applied to the soil in the following rates: treatment BC10—10 Mg × ha−1, treatment BC20—20 Mg × ha−1, treatment BC30—30 Mg × ha−1 and treatment BC0—Control (soil without the addition of biochar). Biochar was mixed the soil arable layer (0–20 cm). Soil samples were collected ten times, once a year—after harvest rye. They were taken from layers: 0–10 cm and 10–20 cm, in six replicates, using 100 cm3 metal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…In addition, Meng [27] found that the soil bulk density was on average reduced by 16%, and meanwhile the capillary porosity was increased by approximately 6% after amending wood and bamboo derived biochar into a Chinese Fir plantation soil. A similar effect was confirmed by one 10-year continuous experiment conducted by Pranagal et al [28]. This benefit may be mainly due to the large specific surface area, and the irregular and fluffy granular structure of biochar, which consequently promoted the formation of a soil porous structure [29].…”
Section: Alleviating the Compaction Of Forest Soilsupporting
confidence: 66%
“…In addition, Meng [27] found that the soil bulk density was on average reduced by 16%, and meanwhile the capillary porosity was increased by approximately 6% after amending wood and bamboo derived biochar into a Chinese Fir plantation soil. A similar effect was confirmed by one 10-year continuous experiment conducted by Pranagal et al [28]. This benefit may be mainly due to the large specific surface area, and the irregular and fluffy granular structure of biochar, which consequently promoted the formation of a soil porous structure [29].…”
Section: Alleviating the Compaction Of Forest Soilsupporting
confidence: 66%
“…Wang et al (2018) found that the application of large particles of biochar significantly inhibited soil evaporation, which was because the addition of biochar promoted the flow of water in capillary pores, thus reducing water vapor transport. In addition, soil nutrients were critical to crops growth, therefore, biochar can improve crop yield and quality by inputting nutrients into the soil (Fu et al, 2022; Glab et al, 2016; Pranagal & Kraska, 2020). The 16.2%–18.6% increase in crop yield with biochar application found in this study was also one of the reasons for the increase in WUE.…”
Section: Discussionmentioning
confidence: 99%
“…farm and municipal wastes), and the gradual shift from coal to more sustainable energy sources has created large global reserves of BCW, and hence, like FYM, these carbonised amendments have worldwide applicability (Amoah-Antwi et al 2020a; Barros et al 2020). Therefore, the utilisation of variable sources of organic amendments such as BIO and BCW contributes to the recovery and valorisation of organic wastes which have implications for the circular economy and sustainability (Barros et al 2020;Pranagal and Kraska 2020).…”
Section: Holistic Assessmentmentioning
confidence: 99%
“…Thus, biochar and BCW improve soil quality by increasing organic matter (OM) content and sorption capacity, which enhance soil aggregation, C sequestration, microbial activity, nutrient retention and pollutant (e.g. heavy metals) immobilisation with knock-on effects on water and air quality (Ouyang et al 2013;Li et al 2018;Amoah-Antwi et al 2020a;Pranagal and Kraska 2020). The enhanced structure, retention and slow chemical release capacities of soil can have variable positive effects on CO 2 , N 2 O, NH 3 and CH 4 fluxes to and then soil nutrient, heavy metal and organic pollutant fluxes to water along surface and near-surface pathways with significant consequences on climate change and water quality (Rose et al 2016;Saha et al 2018;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%